ASSESSING THE IMPACT OF REGULATORY REFORM IN DEVELOPING COUNTRIES1. (August 2014) - Kirkpatrick, Colin
SUMMARY Effective economic governance is a key condition for economic growth and development, and donor support to developing countries has increasingly been focused on regulatory reforms that are intended to enable markets to function more efficiently thereby providing a stable and supportive environment for investment, private sector development, and market‐led economic growth. This article reviews the empirical evidence on the impact of regulatory reform in developing countries. The evidence is broadly consistent with a priori expectations, showing a positive relationship between regulatory reform and improved economic performance. However, various methodological and data problems weaken the robustness of these findings and point to the need to broaden the range of designs and methods for evaluating the results of donor‐supported regulatory reforms in developing countries. Copyright © 2014 John Wiley & Sons, Ltd.